A Correlation Study between Self-esteem and Romantic Jealousy among University Students - Y. Go, Jenina Paula; Chan, Jaeyanne A.; Cruz, Mary Julianne T. Dela; Gomez, Thrissa Marie; Arcinas, Myla M. (Future Science / FSH-PH Publications, 2021)
This correlation study aimed to determine the association between the level of self-esteem and romantic jealousy among selected undergraduate university students from Metro Manila, Philippines. The researchers conducted an online survey with the use of self-administered questionnaires. Purposive non-probability sampling was used to identify the 40 respondents for this study. to gather respondents. Descriptive and inferential statistics. Majority of the respondents were females (23 out of 40) and in their early stage of relationship (1-4 months). Results show that the respondents have a moderate level of self-esteem (median of 3) and high level of romantic jealousy (median of 5). A statistically significant inverse correlation was found between their level of self-esteem and romantic jealousy (r =-0.185, p<.05). The result suggests that the higher their level of self-esteem, the lower the romantic jealousy, i.e. romantic jealousy has no space if one is confident in one's romantic relationship.